2019
DOI: 10.1080/13880209.2019.1577466
|View full text |Cite
|
Sign up to set email alerts
|

Coptidis Rhizoma: a comprehensive review of its traditional uses, botany, phytochemistry, pharmacology and toxicology

Abstract: Context: Coptidis rhizome (CR), also known as Huanglian in Chinese, is the rhizome of Coptis chinensis Franch., C. deltoidea C.Y. Cheng et Hsiao, or C. teeta Wall (Ranunculaceae). It has been widely used to treat bacillary dysentery, diabetes, pertussis, sore throat, aphtha, and eczema in China. Objectives: The present paper reviews the latest advances of CR, focusing on the botany, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
172
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(174 citation statements)
references
References 205 publications
2
172
0
Order By: Relevance
“…It is often widely prescribed by Chinese practitioners for the treatment of high fever, coma, and respiratory diseases [119]. According to Professor Zhao Zhi Li from Shanghai Traditional Chinese Medicine University, Scutellaria baicalensis is acknowledged as a middle class medicine and Forsythia suspense as a low class medicine recorded in Shennong's Classic of Materia Medica from Han dynasty according to its ranking for medicinal value with high class or A level as the most valued in terms of pharmacology, whereas Lonicera japonica has been used as a medicinal plant for the treatment of diseases since the Southern and Northern Dynasty in "Mingyi Bielu" [120,121]. There is a total of 12 companies that manufacture this antidote and one of the manufacturers, Hayao Company's Shuang Huang Lian Kou Fu Ye was categorized as an "A level" list drug, which is the best quality of drugs in TCM according to the categorization in 2019 National health insurance project in China [115].…”
Section: Traditional Chinese Medicine Can Suppress Sars-cov-2 In Vitromentioning
confidence: 99%
“…It is often widely prescribed by Chinese practitioners for the treatment of high fever, coma, and respiratory diseases [119]. According to Professor Zhao Zhi Li from Shanghai Traditional Chinese Medicine University, Scutellaria baicalensis is acknowledged as a middle class medicine and Forsythia suspense as a low class medicine recorded in Shennong's Classic of Materia Medica from Han dynasty according to its ranking for medicinal value with high class or A level as the most valued in terms of pharmacology, whereas Lonicera japonica has been used as a medicinal plant for the treatment of diseases since the Southern and Northern Dynasty in "Mingyi Bielu" [120,121]. There is a total of 12 companies that manufacture this antidote and one of the manufacturers, Hayao Company's Shuang Huang Lian Kou Fu Ye was categorized as an "A level" list drug, which is the best quality of drugs in TCM according to the categorization in 2019 National health insurance project in China [115].…”
Section: Traditional Chinese Medicine Can Suppress Sars-cov-2 In Vitromentioning
confidence: 99%
“…3). Discussion NPC is a common malignant tumor in South China and Southeast Asia (16). The specific etiology of NPC is still unclear, however, it has been reported that NPC is related to EBV virus infection, and methylation of the parkin gene may also promote tumors of NPC (17,18).…”
Section: Correlation Analysis Of Mir-34a and Ki67 Expression Levels Imentioning
confidence: 99%
“…Rhizoma Coptidis (RC), commonly known as Huanglian in China, is the rhizome from the family Ranunculaceae, including Coptis chinensis Franch, C. deltoidei C.Y. Cheng et Hsiaao, and C. teeta Wall . RC, first mentioned in Shennong's Classic of Materia Medica in the Eastern Han Dynasty, has been used to treat various diseases in traditional Chinese medicine (TCM) for thousands of years .…”
Section: Introductionmentioning
confidence: 99%
“…RC, first mentioned in Shennong's Classic of Materia Medica in the Eastern Han Dynasty, has been used to treat various diseases in traditional Chinese medicine (TCM) for thousands of years . Previous studies have demonstrated that RC has activities including anti‐hyperglycemic, anti‐cancer, anti‐bacterial, anti‐hyperlipidemic, anti‐inflammatory, anti‐obesity and anti‐hepatic steatosis . Currently, more than 120 components have been isolated and identified from RC, and alkaloids are most common in plants from RC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation